ENHANCING STUDENT LEARNING OUTCOMES IN CITIZENSHIP EDUCATION THROUGH THE USE OF WORDWALL APPLICATION MEDIA IN ELEMENTARY SCHOOLS - Najibudin (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This study uses Wordwall to improve Citizenship Education (PKn) at An Nadzir Integrated Islamic Elementary School. Wordwall lets users create engaging educational games. This study combines classroom action research (CAR) with two planning cycles: execution, observation, and reflection. The survey included 26 Cinangka District Elementary School grade II pupils. Observation, interviews, questionnaires, and learning outcome tests collected data. Students were more motivated and engaged in learning. Student learning outcomes rose from 57% in cycle I to 88% in cycle II. Wordwall also enhances classroom interaction and collaboration. These data indicate that the Wordwall app improves PKn learning. PKn instructors could try Wordwall for interactive learning. This study also suggests training instructors to use educational technology to boost classroom learning